Correlation between the left atrial low‐voltage area and the cardiac function improvement after catheter ablation for paroxysmal atrial fibrillation. Issue 5 (11th July 2019) - Nakatani, Yosuke; Sakamoto, Tamotsu; Yamaguchi, Yoshiaki; Tsujino, Yasushi; Kataoka, Naoya; Nishida, Kunihiro; Mizumaki, Koichi; Kinugawa, Koichiro
Abstract: Background: The impact of the left atrial low‐voltage area (LVA) on the cardiac function improvement following ablation for atrial fibrillation (AF) is unclear. Methods: In 49 patients with paroxysmal AF who underwent ablation, the left ventricular stroke volume index (SVI) was repeatedly measured using an impedance cardiography until 6 months after ablation. We defined the cardiac function improvement as a 20% increase in the SVI. The LVA (the area with the voltage amplitude of <0.5 mV) was assessed before ablation. Results: The reduced baseline SVI (<33 mL/m 2 ) was observed in 18 (37%) patients. The SVI increased following ablation (from 36 ± 5 to 39 ± 6 mL/m 2, P < .001). We observed the cardiac function improvement in 14 (29%) patients. The LVA was smaller in patients with the improved cardiac function than in those without (8.3% ± 5.2% vs 14.0% ± 8.5%, P = .026). The multivariate analysis revealed that only the LVA was independently associated with the cardiac function improvement (odds ratio, 0.878; 95% confidence interval: 0.778‐0.991, P = .036). Furthermore, LVAs of the anterior (7.9% ± 7.6% vs 18.2% ± 15.5%, P = .022), septal (12.0 ± 7.3% vs 20.7% ± 13.8%, P = .031), and roof walls (6.9% ± 6.0% vs 16.9% ± 15.2%, P = .022) were smaller in patients with the improved cardiac function than in those without. Conclusions: The LVA was related to the cardiac function improvement following ablation in patients with paroxysmal AF.